In Vitro Analysis of Pyrogenicity and Cytotoxicity Profiles of Flex Sensors to be Used to Sense Human Joint Postures - Giovanni Saggio; Luigi Bianchi; Silvia Castelli; Marilina B. Santucci; Maurizio Fraziano; Alessandro Desideri (Sensors, 2014)
Flex sensors can be usefully adopted as mechanical-electrical transducers to measure human joint movements, since their electrical resistance varies proportionally to the angle assumed by the joint under measure. Over time, these sensors have been investigated in terms of mechanical and electrical behavior, but no reports have detailed the possibility of their adoption not just on top but under the human skin of the joint. To this aim, our work investigated in vitro the pyrogenic potential and cytotoxicity of some commercially available flex sensors as a first step toward the necessary requirements regarding their biocompatibility, to predict possible foreign body reactions when used in vivo. Results demonstrated that some specific flex sensors satisfy such requirements.